Aggressive Turn-Around Manoeuvres with an Agile Fixed-Wing UAV. Issue 17 (2016) - Levin, Joshua M.; Nahon, Meyer; Paranjape, Aditya A.
Abstract: This paper investigates an aerobatic manoeuvre performed by an agile fixed-wing unmanned aerial vehicle, with the intent of determining how best the manoeuvre can be automated. The manoeuvre is an aggressive turn-around: a 180 degree reversal of the aircraft's heading, in which the space required for completing the turn is minimized. A comprehensive dynamics model of an agile fixed-wing aircraft is used to design trajectories of the manoeuvre off-line using optimal control. A methodology for evaluating the suitability of controllers for executing the manoeuvre is also presented.